Development of a QCDFR-Based Supplier Performance Weighting Model Using AHP - Bagus Pramulya; Era Fransiska; Mohamad Haifan (Journal of Mandalika Social Science, 2026)
In the manufacturing industry, supplier performance evaluation is a critical aspect of supply chain management, as it directly affects product quality, cost efficiency, and the sustainability of organizational operations. In practice, supplier evaluation processes often face challenges arising from the subjective assignment of weights to evaluation criteria and indicators, which may lead to bias and inconsistencies in decision-making. This study proposes a novel supplier performance weighting model by integrating the Quality, Cost, Delivery, Flexibility, and Responsiveness (QCDFR) framework with the Analytic Hierarchy Process (AHP) to provide a more objective and systematic basis for supplier evaluation. A quantitative descriptive approach was employed through in-depth interviews, field observations, and questionnaire surveys involving expert judgment. The collected data were analyzed using the AHP method to determine the relative priorities and weights of each criterion and indicator. The results identified five evaluation criteria and thirty-four indicators: Quality (6), Cost (8), Delivery (9), Flexibility (4), and Responsiveness (7). Quality was assigned the highest priority weight (0.46), followed by Cost (0.26), Delivery (0.12), Flexibility (0.08), and Responsiveness (0.08). Moreover, all pairwise comparison matrices achieved Consistency Ratio (CR) values below 0.10, confirming the reliability and consistency of the proposed weighting model. The proposed model provides a practical and objective framework for supporting supplier performance evaluation and decision-making processes.